2018
DOI: 10.1002/aur.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced distractor interference in neurotypical adults with high expression of autistic traits irrespective of stimulus type

Abstract: Attention atypicality is evident in autism spectrum disorder (ASD) and its broader phenotype with previous studies suggesting that in some cases participants can be more efficient at ignoring distracting irrelevant information. However, it is not clear to what extent this improved filtering capacity is driven by perceptual atypicality, such as local bias or atypical face processing, which is also sometimes reported in these populations. For instance, better ability to ignore the global aspect of a display coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Notably, these results also suggest that unlike reactive control, which appears to facilitate context adaptation in individuals with high positive schizotypy and low focus of attention (Figure 4c), proactive control facilitates context adaptation in individuals with low positive schizotypy and high focus of attention (Figure 4a). This is consistent with previous research suggesting that individuals with contrasting autistic and positive schizotypy trait profiles appear to be differentially reliant on proactive versus reactive control strategies (Abu-Akel et al, 2018;Niendam et al, 2014;Spaniol et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Notably, these results also suggest that unlike reactive control, which appears to facilitate context adaptation in individuals with high positive schizotypy and low focus of attention (Figure 4c), proactive control facilitates context adaptation in individuals with low positive schizotypy and high focus of attention (Figure 4a). This is consistent with previous research suggesting that individuals with contrasting autistic and positive schizotypy trait profiles appear to be differentially reliant on proactive versus reactive control strategies (Abu-Akel et al, 2018;Niendam et al, 2014;Spaniol et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Since the correlation analyses in our study showed only support for the association between positive schizotypal traits and reactive control tendencies, the contribution of increasing autistic traits to improvement in context adaptation under proactive control remains unresolved. However, if individuals with high schizotypal traits are similar to patients with schizophrenia in that they can engage reactive but not proactive control mechanisms (Lesh et al, 2013), the co-presence of autistic traits, which has been associated with greater utilization of proactive control strategies (Spaniol et al, 2018), appears to somehow restore the ability for these individuals to flexibly engage proactive control. It should be noted, however, that while healthy participants are expected to flexibly engage these modes of cognitive control (Marklund & Persson, 2012), our results suggest that this might be maximally present among individuals in whom both high levels of autistic and positive trait dimensions are co-present.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations